Bundesfeier 1929. Fahne hissen - Nicht Anwendbar (ETH-Bibliothek Zürich, Bildarchiv, 1929)
Download und Nutzung frei : Botschaft der Postkarte: Dear Sir I have been in Iceland & Norway this Summer it was a fine holiday. Always pleased to heear from you Ever yours A. Feller. Poststempel 20.12.1929